2012
DOI: 10.1161/hypertensionaha.111.179382
|View full text |Cite
|
Sign up to set email alerts
|

Fish, n-3 Fatty Acids, and Cardiovascular Diseases in Women of Reproductive Age

Abstract: Abstract-Previous studies have indicated a protective effect of long-chain n-3 polyunsaturated fatty acids (LCn3FAs) against cardiovascular disease; however, women are underrepresented in cardiovascular research. The aim of this study was to explore the association between intake of LCn3FAs and the risk of cardiovascular disease in a large prospective cohort of young women (mean age at baseline: 29.9 years [range: 15.7-46.9] Key Words: cardiovascular diseases Ⅲ fatty acids Ⅲ epidemiology Ⅲ follow-up study Ⅲ wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 44 publications
(42 reference statements)
2
21
0
1
Order By: Relevance
“…The beneficial effects of fish consumption on both CVD [6,7,8,9,10,11,12] and DM2 have been described previously [13,14,15]. Since MetS consists of several of the same risk factors as CVD and DM2, one would expect fish consumption to reduce the risk of MetS as well.…”
Section: Introductionmentioning
confidence: 80%
“…The beneficial effects of fish consumption on both CVD [6,7,8,9,10,11,12] and DM2 have been described previously [13,14,15]. Since MetS consists of several of the same risk factors as CVD and DM2, one would expect fish consumption to reduce the risk of MetS as well.…”
Section: Introductionmentioning
confidence: 80%
“…In one study, no association with coronary calcification was found (102). However, six of the studies found a significant risk reduction for CVD, but in most cases only for specific outcomes (ischemic stroke, sudden cardiac death (SCD), fatal CHD, and CHD) (95, 96, 98, 100, 103105). In two studies with similar outcomes, no association was found (107, 108).…”
Section: Resultsmentioning
confidence: 99%
“…One of the studies found that the degree of risk reduction on sudden coronary mortality decreased with age in men and was not significant after the age of 65 years (100), which could explain the lack of an effect in the studies where most of the cases were above that age (99, 101, 102, 106). One of the recent Scandinavian studies did find an increase in an overall risk of CVD as well as in all its sub-disease classes (CHD, stroke, and hypertension) at very low n-3 LCPUFA intake (≤0.06 g/day) compared with intakes >0.73 g/day in women aged 16–47 with a follow-up of up to 12 years (105). The typical effect size was a risk reduction of 30–60% at intakes >0.2 g/day.…”
Section: Resultsmentioning
confidence: 99%
“…In a large study of over 48, 000 women in the Danish National Birth Cohort, women of reproductive age who had little to no fish intake had a significantly higher risk of CHD as compared to women with the highest levels of fish intake (hazard ratio 3.80, 95 % CI 1. 53-9.42) [17].…”
Section: Dietmentioning
confidence: 99%